Economic viability of high-performance cycle systems: Energy and cost efficiency insights - Rui Xie; Xiaojuun Deng; Yuannxing Yin; Dilafruz Fayziyeva; Elchin Eyvazov; Fu Liu (Energy Strategy Reviews)
This study evaluates the economic viability of high-performance cycle systems through a comprehensive analysis of energy and cost efficiency factors in thermal energy storage technologies. Our research identifies significant cost-benefit advantages of innovative design approaches over conventional systems in industrial applications. Through rigorous economic modeling and performance testing, we analyzed operational efficiency, capital investment requirements, and long-term financial returns. Results demonstrate that the advanced designs deliver substantial economic benefits by reducing operational times by 33.2%, enhancing energy utilization rates by 48.4%, and improving overall system efficiency by 8.3% compared to traditional approaches. Optimized system configurations further enhanced performance metrics and cost-effectiveness. Our economic analysis reveals significant potential for operational cost reduction and energy efficiency improvements in industrial applications, with projected payback periods shortened by approximately one-third. These findings underscore the economic viability of implementing innovative designs in high-performance cycle systems, with implications for reducing operational costs, improving return on investment, and enhancing market competitiveness in energy-intensive industries. Future research directions include scaling applications for various industrial sectors and quantifying broader economic and sustainability impacts.